Sapore, Sapere: por uma poética dos cinco sentidos em Italo Calvino - Bruna Fontes Ferraz (2018)
When Italo Calvino commented on the book he was writing that would approach the five senses, he stated that contemporary man had lost their usages. Such book, that came to be posthumously published with the title Under the jaguar sun, brought about reflections that guided this research in its purpose of investigating the relation between language and five senses in the work of the Italian writer. Looking into the possible withering of senses and the decline of experience in modern man, we hereby inquire if language would turn man sensitive to external stimuli, or if it would allow sensuous experiences to become accessible to them. Words, in creating universes of senses regulated by the absence of the referent, would not let us forget the absent, therefore complementing it with their connotative force. Hence, both objects and the signs that represent them may exert physical action over our body: a word may stimulate senses and awake memories; we are literally touched by a text. In order to reach this sensation of concreteness, in order for the word to invoke its referent and also become its vestige, language must be used with precision, seeking to describe a range of sensations. Calvino, the short-sighted writer, wrote from the bottom of the opaque, filling in the nebulous and obscure portions with his imagination. Broadening critical perspectives that associate the Italian writer to a more intellectualist and rationalist line of thought, our aim is to foreground the sensorial side of some of the writings of Calvino, who also exercised with a sensitive language, resorting to the five senses, to the sapore of the world, in order to reach multiple saperi.